NorLeu(3)-Angiotensin (1-7) [DSC127] as a Therapy for the Healing of Diabetic Foot Ulcers - Rodgers, Kathleen E. (Adv Wound Care (New Rochelle), 2015)
Significance: Diabetes is a disorder that is well known to delay wound repair resulting in the formation of colonized chronic wounds. Over their lifetime, diabetic patients have a 25% incidence of foot ulcers (DFUs), which contribute to increased risk of morbidity, including osteomyelitis and amputations, and increased burden to the healthcare system. Recent Advances: The only active product approved for the treatment of diabetic ulcers, Regranex(®), is not widely used due to minimal proven efficacy and recent warnings added to the Instructions for Use. A novel topical agent that accelerates healing and increases the proportion of fully healed DFUs, DSC127 [aclerastide; active ingredient, NorLeu(3)-angiotensin (1-7) (NorLeu(3)-A(1-7))], is recruiting patients in Phase III clinical trials (NCT01830348 and NCT01849965). NorLeu(3)-A(1-7) is an analog of the naturally occurring peptide, angiotensin 1-7. The mechanisms of action include induction of progenitor proliferation, accelerated vascularization, collagen deposition, and re-epithelialization. Critical Issues: Current modalities for the treatment of DFUs include strict offloading, bandaging, debridement and, on a limited basis, application of Regranex. Novel potent therapies are needed to combat this significant burden to the diabetic patient and the healthcare system. Future Direction: Preclinical and clinical research shows that DSC127 is highly effective in the closure of diabetic wounds and is superior to Regranex in animal studies. Clinical development of DSC127 as a topical agent for the healing of DFU is underway. Further investigation into the mechanisms by which this product accelerates healing is warranted.